Post-Wage Politics and the Rise of Community Capitalism. (June 2018) - van Dyk, Silke
This article discusses new patterns of precariarization and informalization beyond waged labour. Against a backdrop of multiple social changes, there is a new era of social reproduction based on the interplay between a politics of post-waged work and a politics of community, involving activities outside the realms of market, state and family. Whereas the implications of family-based care work have long been highlighted, the community-based political economy of the 'post-wage regime' has yet to be analysed. Taking Germany as an example, the article describes how the state is actively involved in promoting and exploiting post-waged work. At the same time, community projects and grassroots activities contribute to the social reproduction of livelihoods, often becoming an active part of the precarious post-wage regime. The question is raised whether or not these interweaving developments herald a new era of community capitalism.